The accidental taxonomist - Hedden, Heather (The Accidental Library, 2016)
The Accidental Taxonomist is the most comprehensive guide available to the art and science of building information taxonomies. Heather Hedden--a leading taxonomy expert and instructor--walks readers through the process, displaying her trademark ability to present highly technical information in straightforward, comprehensible English.